Perspektif Mahasiswa UIN Sumatera Utara 2020 Pecinta K-POP tentang Personal Branding Fuadh Naim di Instagram - Tifani Liusnimun; Tengku Walisyah (Mahesa Research Center, 2024)
Personal Branding or Personal Branding will be easier if managed using the internet via social media. Personal Branding is not only done by professionals in the world of work, this can also be done by a preacher who preaches via social media to increase your trust in him. The purpose of this research is to find out the perspective of KPI UINSU 2020 students who like K-Pop regarding the Personal Branding built by Fuadh Naim in preaching on his social media, this is because K-Pop lovers will be more subjective in assessing the Personal Branding built by Ustad Fuadh Naim because it suits them, namely Korean culture. This research uses a type of field research using a qualitative approach, and data collection techniques using 3 methods, namely observation, interviews, and documentation. The data analysis used in this research is narrative analysis. The results of this research show that the eight Personal Branding concepts coined by Peter Montoya are Specialization, Leadership, Personality, Difference, Appearance, Unity, Firmness and Good Name. This is found in Fuadh Naim's self and preaching seen from the informants' perspective in this research. This shows that Fuadh Naim has uniqueness in his personality and preaching so that his preaching can be easily accepted by his mad'u.